2019
DOI: 10.1111/liv.14239
|View full text |Cite
|
Sign up to set email alerts
|

The ATG16L1 gene variant rs2241880 (p.T300A) is associated with susceptibility to HCC in patients with cirrhosis

Abstract: Background and aims: Protein and organelle turnover by autophagy is a key component to maintain cellular homeostasis. Loss of the autophagy protein ATG16L1 is associated with reduced bacterial killing and aberrant interleukin-1β production, perpetuating inflammation and carcinogenesis. Here we hypothesized that the functional p.T300A gene variant in ATG16L1 is associated with an increased risk for hepatocellular carcinoma (HCC) in cirrhosis. Methods:A case-control study was performed using a prospective deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“… 151 The role of ATG16L1 loss-of-function alleles has also been reported for other cancers than HNSCC. Indeed, rs2241880 has been described as a risk factor both for developing hepatocellular carcinoma in the context of cirrhosis, 152 breast cancer, 153 and gastric cancer. 154 Moreover, the ATG16L1 AG genotype was found to be associated with an earlier age at diagnosis of melanoma.…”
Section: Resultsmentioning
confidence: 99%
“… 151 The role of ATG16L1 loss-of-function alleles has also been reported for other cancers than HNSCC. Indeed, rs2241880 has been described as a risk factor both for developing hepatocellular carcinoma in the context of cirrhosis, 152 breast cancer, 153 and gastric cancer. 154 Moreover, the ATG16L1 AG genotype was found to be associated with an earlier age at diagnosis of melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ATG16L1 proteins were upregulated in HBV‐related HCC compared to adjacent nontumor tissues 29 . Furthermore, ATG16L1 and ATG5 gene polymorphisms are linked to susceptibility to multiple diseases 30–32 . To date, the influence of ATG16L1 and ATG5 polymorphisms on HBV infection has not been reported in central China.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, ATG16L1 and ATG5 gene polymorphisms are linked to susceptibility to multiple diseases. [30][31][32] To date, the influence of ATG16L1 and ATG5 polymorphisms on HBV infection has not been reported in central China. Hence, to further investigate the role of autophagy in HBV infection, we conducted this study to confirm the influence of ATG (ATG16L1 and ATG5) gene polymorphisms on susceptibility to HBV infection and the progression of HBV-related HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The function of beclin-1 is inhibited by B-cell CLL/lymphoma 2, and thus, it has been demonstrated that beclin-1 acts as a tumor suppressor [ 22 , 23 ]. ATG proteins, such as ATG3, ATG12, and ATG16L1, are also demonstrated to have anti-oncogenic properties [ 24 , 25 , 26 , 27 ]. The impairment of autophagy causes the accumulation of P62, leading to the development of HCC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%